Aging and pension reform: extending the retirement age and human capital formation*. (8th June 2015) - VOGEL, EDGAR; LUDWIG, ALEXANDER; BÖRSCH-SUPAN, AXEL
Abstract: Projected demographic changes in industrialized and developing countries vary in extent and timing but will reduce the share of the population in working age everywhere. Conventional wisdom suggests that this will increase capital intensity with falling rates of return to capital and increasing wages. This decreases welfare for middle aged asset rich households. This paper takes the perspective of the three demographically oldest European nations – France, Germany and Italy – to address three important adjustment channels to dampen these detrimental effects of aging in these countries: investing abroad, endogenous human capital formation, and increasing the retirement age. Our quantitative finding is that endogenous human capital formation in combination with an increase in the retirement age has strong implications for economic aggregates and welfare, in particular in the open economy. These adjustments reduce the maximum welfare losses of demographic change for households alive in 2010 by about 2.2 percentage points in terms of consumption equivalent variation.